2004
DOI: 10.1002/jnr.20360
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of growth and differentiation of cone oil droplets in the chick retina

Abstract: Avian cone photoreceptors have an oil droplet in the outer portion of their inner segment that acts as a long-pass cut-off filter between incident light and visual pigment. Chick cone droplets are mainly red, orange, yellow, green, and colorless, and the colors are due to three carotenoid pigments with characteristic absorption spectra. Little is known of the differentiation of this organelle, the natural marker of cones, and the little that is known is largely controversial. We used flat whole-mounts of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…We found that at all timepoints examined, the data fall on the same curve as the data from P15 (inset in Figure 6A). Since oil droplet pigmentation first becomes apparent in the peripheral retina around E16–17 and full pigmentation of all the red cones first appears somewhat later [53], E18 was the earliest point at which we could reliably distinguish all cones of this type. We therefore conclude that, at least for red cones, the adult pattern of spatial organization is already achieved at the earliest point at which oil droplets can be distinguished.…”
Section: Resultsmentioning
confidence: 94%
“…We found that at all timepoints examined, the data fall on the same curve as the data from P15 (inset in Figure 6A). Since oil droplet pigmentation first becomes apparent in the peripheral retina around E16–17 and full pigmentation of all the red cones first appears somewhat later [53], E18 was the earliest point at which we could reliably distinguish all cones of this type. We therefore conclude that, at least for red cones, the adult pattern of spatial organization is already achieved at the earliest point at which oil droplets can be distinguished.…”
Section: Resultsmentioning
confidence: 94%
“…Other lines of evidence support this possibility. For instance, photoreceptor oil droplets appear first in the center and later in the periphery (22), and the developmental timing and distribution of wavelength-specific cone opsin expression also differs from center to periphery (1).…”
Section: Discussionmentioning
confidence: 99%
“…8). The isolated photoreceptors were readily identified in the dissociates as rods, double cones, and single cones based on their structure and the shape of their outer segments; single cone subtypes were distinguished based on their characteristic oil droplets (López et al, 2005). These identification criteria have been verified by PCR of individual cells (Wahlin et al, 2004;Huang and Adler, 2005;Wahlin et al, 2007).…”
Section: Subcellular Localization Of Immunoreactivity For Mbnl1 and 2mentioning
confidence: 99%